Comparative analysis of seagrass habitat structure: distinct patterns at semi-enclosed and open sites in South Sulawesi, Indonesia - Mirdayanti; Kadir, Nadiarti Nurdin; La Nafie, Yayu A (Ecological Questions, 2024)
Habitat structure in the seagrass ecosystems are crucial for coastal biodiversity and substrate stability. The purpose of this research conducted from June to December 2021 in South Sulawesi Province, Indonesia was to examine the habitat structure of seagrass beds at two sites with different levels of exposure: Puntondo (semi-enclosed bay) and Batu Kalasi (exposed). Species identification, non-metric multidimensional scaling (nMDS), Bray Curtis cluster analysis, similarity percentage (SIMPER), Particle Size Analysis (PSA), and satellite imagery were used to evaluate complexity, heterogeneity, sediment particle size, and extent. The presence of macroalgae and coral species at Batu Kalasi, likely related to substrate condition, contributed to significant differences in seagrass community composition. The nMDS and Bray Curtis cluster analyses revealed patterns of complexity, while satellite imagery revealed habitat heterogeneity. Seagrass meadow tracking showed a larger and more patchy area in Puntondo Village, measuring 164,318 m², while in Batu Kalasi Island, it only reached 136,901 m². The findings underscore the need for tailored conservation strategies for seagrass ecosystems, in particular to address the specific challenges observed at each site, emphasizing the importance of understanding and preserving diverse coastal environments.